Principles for establishment of the stem cell bank and its applications on management of sports injuries - Bao-Shi Fan; Yang Liu; Ji-Ying Zhang; You-Rong Chen; Meng Yang; Jia-Kuo Yu (Stem Cell Research & Therapy, 2021)
Abstract Background The stem cells of the stem cell banks have prominent problems for insufficient sources, easy contamination, unstable biological characteristics after serial subcultivations, and high cost. Methods After collecting the construction processes of the existing stem cell banks and suggestions from authoritative experts in the past 10 years, 230 reference principles were obtained, and finally, the principles of “5C” for the establishment of modern standardized stem cell banks were summarized, and their related applications on the management of sports injuries were reviewed as well. Results The basic principles of “5C” for the establishment of modern standardized stem cell banks include (1) principle of informed consent, (2) confidentiality principle, (3) conformity principle, (4) contamination-free principle, and (5) commonweal principle. The applications of stem cells on repairs, reconstructions, and regenerations of sports injuries were also reviewed, especially in tissue-engineered cartilage, tissue-engineered meniscus, and tissue-engineered ligament. Conclusions The proposal of the basic principles of “5C” is conducive to relevant stem cell researchers and clinical medical experts to build modern stem cell banks in a more standardized and efficient manner while avoiding some major mistakes or problems that may occur in the future. On this basis, stem cells from stem cell banks would be increasingly used in the management of sports injuries. More importantly, these days, getting stem cell samples are difficult in a short time, and such banks with proper legal consent may help the scientific community.